Price Changes in A Limited Time in Home Shopping Program on RTV Television Media From The Perspective of Islamic Law - Arianti, Farida; Yunarti, Sri (al-'adalah, 2022)
This study aims to examine the views of Islamic law on price changes in a limited time in the Home shopping program on RTV television media and the implications for buying and selling activities in the program. This type of research is field research using a phenomenological approach. The data collection used observation techniques on RTV television social media and YouTube promo shows for home shopping products. The study results concluded that product sales in the home shopping program contain an element of uncertainty (gharar) by mixing prices over time; because the product is sold at a discount, that price is added to other goods at a specific price, which is an additional bonus. This activity causes the price to change from the price of the initially offered item and then added to the bonus item that must also be paid. This price is only valid for a short period, and then, after the promotion time is up, the price of the item being sold returns to the pre-discount price so that the selling price of the product offered is unclear (gharar) and contains an element of speculation which is not permitted in Islamic teachings.